DINAMIKA POPULASI DAN AKTIVITAS BIOLOGIS JAMUR ISOLAT PELET KOMPOS PADA BERBAGAI DOSIS PUPUK NPK - Irfan, Mokhamad; Aryanti, Ervina (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
The addition of inorganic fertilizers to overcome the limitations of organic fertilizers in the form of compost pellets affects the microbial life within them. Meanwhile, the biological activity of fungi as biocontrol agents, biofertilizers, decomposers, and plant growth promoters is highly essential. This study aimed to determine the optimal NPK fertilizer dosage for compost pellets. The research was conducted from October to December 2024 at the PEMTA Laboratory, UIN Suska Riau. The research employed a qualitative descriptive method with six treatment levels. The results showed that the treatment without NPK addition produced 7 fungal isolates with a population of 5.0 × 106 cfu/g; addition of 1% NPK yielded 11 isolates with a population of 3.5 × 106 cfu/g; 2% NPK resulted in 10 isolates with 1.0 × 105 cfu/g; 3% NPK had 7 isolates with 6.0 × 105 cfu/g; 4% NPK showed 4 isolates with 5.0 × 105 cfu/g; and 5% NPK had 7 isolates with 1.2 × 105 cfu/g. Referring to the original source of the isolates, which were derived from compost shaped into pellets, the biological activities of the fungal isolates were predominantly decomposers, followed by phosphate-solubilizing fungi. The number of isolates acting as biocontrol agents and producers of plant growth regulators (PGRs) was relatively low.